Caracterização geológica e estrutural da porção centro-norte do greenstone belt de Faina, Faina-GO - Carneiro, Henrique Pelorca [UNESP] (2013)
The area where the study was conducted is located in the central-western state of Goias. It geologically inserts the northern portion of the Greenstone Belt of Faina which belongs to the Archean terranes that fits in Brasília Fold Belt and Tocantins Structural Province. This region is known for its greenstone lode gold potential and it was heavily exploited by pioneers and prospectors, leaving many records for where they have been through. Preliminary work done by Orinoco Brasil Mineração in their required areas at the region showed that the environment is promising for gold mineralization and that the ore is controlled by structures. Therefore the objectives of this work were the geological and structural mapping in semi detail scale to improve geological, stratigraphic and structural controls present attributing possible ore understanding. With the development of the work there were recognized on the desktop three structural domains separated by a thrust fault. For each domain were discriminated the geological units ranging in gneisses, quartzites formed from coarse sediments arcoseanos, and schists. By mapping structures there were found five deformation phases, Dn-2, Dn-1, the Dn event that generated the main foliation (Sn) in high representation and two post-stages Dn with brittle late manifestations. The detail mapping of the Rattlesnake Gallery showed that the mineralized quartz vein is consistent with axial-plane foliation Sn-2 belonging to the oldest deformation Dn-2 phase and that the high grade is distributed in the hinge region folds of the same phase